Grain-size distribution of Pleistocene loess deposits in northern Iran and its palaeoclimatic implications. (30th January 2017) - Wang, Xin; Wei, Haitao; Khormali, Farhad; Taheri, Mehdi; Kehl, Martin; Frechen, Manfred; Lauer, Tobias; Chen, Fahu
Abstract: The loess deposits in northern Iran are located in a key region connected to the European and central Asian loess belts. However, the lack of previous detailed sedimentological and palaeoclimatic studies of the Pleistocene loess in the region limits our understanding of the nature of ancient aeolian processes and loess history in the mid-latitudes of Euro-Asia as a whole. Here, we present the results of grain-size analyses of the Pleistocene loess from the so-called Iranian Loess Plateau (ILP) in northern Iran. Our results reveal that the grain-size distribution of the deposits is characterized by trimodal and bimodal distributions, comprising a dominant well-sorted coarse dust component (ca. 7–75 μm), a small poorly-sorted fine dust component (ca. 2–7 μm), and a minor pedogenic clay component (<2 μm). The dominance of the coarse dust component in the samples suggests that the main part of the Pleistocene loess in northern Iran was transported predominantly by the local low-level winds from proximal source regions. The modal size of the coarse dust component is systematically coarser in the lower Pleistocene loess succession than in the lower Pleistocene loess–palaeosol sequence, indicating a progressively intensifying wind strength during the Pleistocene. The proportion of the clay fraction (<2 μm) decreases systematically from the lower Pleistocene to the upper Pleistocene loess strata, suggesting a relatively drier and colder climate in northern Iran during the late Pleistocene than during the early Pleistocene.